UPAYA MENINGKATKAN NASIONALISME SISWA MELALUI PENDEKATAN CRT PADA PEMBELAJARAN PENDIDIKAN PANCASILA KELAS II SD NEGERI MODEL TERPADU MADANI - Anggriani Kasaraeng; Dian C Anggraeni (EDU RESEARCH, 2024)
This study aims to enhance student’s nationalism in Pancasila Education subjects using the CRT learning pedagogy. This research is a classroom action research with the subjects being class II student’s at Model Terpadu Madani elementary school, Mantikulore sub-district, Palu City, with a total of 20 student’s. Data analysis consisted of teacher activity observation sheets, student activity observation sheets, and student nationalism questionnaires. Implementation of pre-action showed that student nationalism was still relatively low. In cycle I and cycle II, student nationalism was 82% and 89%. The results of cycle I and cycle II teacher activities were 75 and 83. The results of student activity in cycle I and cycle II were 72 and 86. Based on these results, it can be concluded that Pancasila Education using the CRT learning pedagogy can increase student nationalism in class II of SD Negeri Model Terpadu Madani.